Integration of Cognitive Therapy and Mindfulness: Impact on Adolescent Mental Health - Tri Wahyuni; Lusiana Rahmadani Putri; Sri Nur Rahmi (Yayasan Adra Karima Hubbi, 2024)
Adolescents face increasing mental health challenges such as anxiety, depression, and stress due to social, academic, and developmental pressures. While cognitive therapy is effective in addressing these issues, integrating mindfulness practices may enhance therapeutic outcomes by promoting emotional regulation and reducing psychological distress. However, research on this combined approach for adolescents remains limited. This study evaluates the effectiveness of integrating cognitive therapy and mindfulness in improving adolescent mental health. A randomized controlled trial (RCT) was conducted with 120 adolescents aged 13-18, divided into two groups: the experimental group receiving both cognitive therapy and mindfulness, and a control group receiving only cognitive therapy. Quantitative data was collected through pre- and post-intervention assessments using the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and Perceived Stress Scale (PSS). Results revealed that the experimental group experienced a 45% reduction in anxiety, a 50% decrease in depression, and a 40% reduction in stress, compared to the control group. The integrated therapy group also reported improved emotional regulation and resilience. The study concludes that combining cognitive therapy with mindfulness is more effective in promoting adolescent mental health than cognitive therapy alone. This approach offers a holistic framework, suggesting its potential for broader therapeutic interventions.